TETRACYCLINE RESISTANCE AND DISCOLORATION OF TEETH: A COMPREHENSIVE STUDY ON DRUG RESISTANCE AND ITS IMPLICATIONS IN THE FEDERAL AREA OF PAKISTAN - BATOOL, M; JAMALI, M; SIDDIQUE, HF; JAVAID, A; RUK, M; UJAN, JA; SOLANGI, SP; SOOMRO, MA; IRAM, T; BILAL, M (Biological and Clinical Sciences Research Journal, 2023)
Tetracycline antibiotics have been pivotal in managing bacterial infections in Pakistan and globally. However, the rampant misuse and overuse of tetracyclines have catalyzed the emergence of antibiotic resistance, presenting a pressing public health challenge. Additionally, the administration of tetracyclines during tooth development can result in tooth discoloration, exerting a profound impact on oral health and the overall quality of life. This research paper delves into assessing the prevalence of tetracycline resistance within the Federal Area of Pakistan, scrutinizes the interplay between tetracycline usage and tooth discoloration by enlisting 682 participants, and comprehensively evaluates the implications of antibiotic resistance on public health within the region. A rigorous examination of tetracycline resistance in the Federal Area of Pakistan comprised an extensive survey involving 682 individuals. The study encompassed diverse age groups and demographic characteristics to ensure a representative sample. The participants were interviewed, and their medical histories were scrutinized to establish the extent and patterns of tetracycline usage. Subsequently, dental examinations and assessments were carried out to identify cases of tooth discoloration associated with tetracycline exposure. Bacterial isolates from clinical specimens were subjected to susceptibility testing to determine the prevalence of tetracycline resistance in the region. The findings of this study revealed a substantial prevalence of tetracycline resistance among bacterial isolates in the Federal Area of Pakistan. Furthermore, the investigation demonstrated a significant correlation between tetracycline usage during tooth development and tooth discoloration in the surveyed population. The high incidence of tetracycline-induced tooth discoloration emphasized the need for increased awareness regarding the judicious use of antibiotics, especially in vulnerable populations. Tetracycline resistance in Pakistan's Federal Area is a pressing concern. Irresponsible use during tooth development can cause discoloration. To combat resistance, regulate use, educate the public, and promote alternative treatments. An integrated approach is urgently needed to protect public health.